Implementation of Problem-based Learning in Improving Student Cognitive Learning Outcomes in Plant Ecology Courses - ilma, Silfia; Wijarini, Fitri (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2024)
This research aims to investigate the effectiveness of problem-based learning in improving student learning outcomes. This research uses a classroom action research approach. Data collection techniques are observation and learning outcomes tests. The research results show that problem-based learning makes a major contribution to improving student learning outcomes. In cycle 1 the lowest average learning outcome was 65.50 and the highest was 77.33. Meanwhile in cycle 2 the lowest average learning outcome was 71.33 and the highest was 82. Problem-based learning provided a good response for students to understand the concept of plant ecology. Apart from that, problem-based learning can motivate students to analyze the causes and find solutions to environmental problems.